Critical Thinking in Teacher Education: Course Design and Teaching Practicum - Angeliki Lithoxoidou; Triantafyllia Georgiadou (MDPI AG, 2023)
Critical Thinking is considered a key component of Higher Education that supports graduates' preparation for the labor market. However, in the field of teacher education more research is needed to support student-teachers with regard to the complexity of schools. It is considered that a teaching practicum can set the stage for the cultivation of Critical Thinking skills and dispositions, as student-teachers have to face real problems and be led to decision-making. The paper presented here describes the curriculum transformation of courses offering theoretical lectures and teaching practicum in the Department of Primary Education, University of Western Macedonia. After focus group discussion with in-service teachers, the Critical Thinking skills and dispositions considered necessary for teacher education were thoroughly described and utilized for the course design. The courses were modified to include a variety of teaching strategies following the direct infusion approach for training in Critical Thinking with the aim of promoting reflective practices for fostering student-teachers' critical reflection. In this way, they can be empowered regarding their professional development.